Implementasi Kebijakan “Tabu Beusaree Hase Meulimpah” dalam Pencegahan Gagal Panen di Kabupaten Nagan Raya - Pratama, Agus; Macella, Agatha Debby Reiza; Mardhiah, Nellis; Jonsa, Alimas (Bahasa Indonesia, 2024)
This research aims to find out how the policy on planting patterns and rice field harvesting schedules is implemented simultaneously with the philosophy of "Tabu Beusaree Hasee Meulimpah" in preventing crop failure in Nagan Raya Regency. Based on initial observations, there are still villages that have not implemented a simultaneous rice planting pattern and several villages have experienced crop failure. The method used in this research is a qualitative method with a descriptive approach. The theory used is Edward III's implementation theory. Based on the research results, policy implementation has been implemented in accordance with the provisions but is not yet optimal. The main obstacle is resources. From the policy implementation sector, the Department of Agriculture still lacks extension officers, limited budget, supporting facilities such as irrigation are not yet able to supply water simultaneously for the needs of farmers at once in each sub-district. In general, this policy cannot be implemented simultaneously in Nagan Raya Regency because it is constrained by water distribution factors. Even though there are obstacles in implementation, rice productivity results in Nagan Raya Regency are experiencing a surplus.